THE DEFAULT IN ISLAMIC PEER TO PEER LENDING: AN APPLICATION OF THE GENERAL STRAIN THEORY - Dety Nurfadilah; Dida Nurhaida; Sudarmawan Samidi (Bank Indonesia, 2022)
While the Islamic peer to peer (P2P) lending is useful especially during the present Covid-19 Pandemic, its default risk remains high. In this study, we apply the extended general strain theory to investigate borrowers’ default intention on the Islamic P2P lending during the pandemic period. Using the SEM-PLS method to analyse data gathered from a survey, we find economic pressure and socialization difficulty to be significant in increasing negative affects (life dissatisfaction, perceived unfairness, and inferiority feeling) and hence indirectly affecting the willingness to repay. Further, we find that socialization difficulty does not seem to have direct influences on default intention. Finally, moral norms appear to be a significant moderating factor in the framework. These should contribute to a better scoring system of the Islamic P2P lending.